Leader and elite positioning in hierarchical system of power distribution: Russian option - Ponedelkov, Alexander Va. (2018)
In article evolution of leader and elite imperious positioning within hierarchical system of the imperious relations is considered in the context of the designated world political dynamics ("power vertical"). It is specified change of model of leader representation of the leading head of the state (V. V. Putin): from constituent - to transformational (according to J. Burns). On the basis of data of expert poll parallel changes at the regional and elite level - in their accompanying and interfering aspects are shown.